Issues and dilemmas facing public and private sector organisations in the effective implementation of BPR - Braganza, Ashley; Myers, Andrew (Cranfield School of Management, 1995)
Business process re-engineering (BPR) is a recent change phenomena that has grabbed the attention of those working in public sector and private sector organisations. In the organisational sense BPR is identified as a key strategic initiative for achieving business improvement in the 1990s. The failure rate of such initiatives once undertaken, however, is reported to be quite high. Why should that be? This article provides some evidence as to why this could be the case. It draws on current literature which centres on three key debates, namely: classifying, planning and managing a BPR initiative. Each of these debates is discussed. There is also a lack of empirical evidence of the importance and difficulties organisations face when undertaking a BPR initiative. It is all very well saying that you should follow a set plan for such an initiative, yet there is no indication as to how difficult it is to implement each stage of that plan. Hence, the Information Systems Research Centre, based at Cranfield School of Management, wished to address this issue. The Centre undertook a survey of managers working in the public and private sector attending a Symposium. Five success factors were identified as key to the implementation of a BPR initiative, namely: 1. induction, 2. providing skills, 3. commitment to the project, 4. changing roles and systems, and 5. changing culture, attitudes and behaviour. The relative importance, difficulties and implications of these are discussed.